Enhancement of gas permeation properties of polybenzimidazoles by systematic structure architecture - Kumbharkar, Santosh C.; Karadkar, Prasad B.; Kharul, Ulhas K. (Journal of Membrane Science, 2006)
Systematic structural variations in thermally stable polybenzimidazole (PBI) are explored that led to a substantial improvement in gas permeation properties. Physical property determinations revealed that incorporation of hexafluoroisopropylidene and tert-butyl groups led to amorphous polymers with slightly lowered thermal stability and decreased chain packing. PBI based on 4,4'-(hexafluoroisopropylidene)bis(benzoic acid) and 5-tert-butyl isophthalic acid exhibited 10-40 times higher permeability, while changes in selectivities for industrially important pairs ranged from modest decrease of 75% or less than that of PBI based on isophthalic acid. The O-2/N-2 selectivity was almost doubled in case of PBI based on 5-tert-butyl isophthalic acid. Gas diffusion coefficients were estimated from solubility and permeability coefficient determinations. These, along with dual-mode sorption parameters estimated from sorption isotherms provided an insight towards variations in permeation behavior. The permeability predictions for heavier gases in isophthalic acid based PBI correlated well with physical properties. The occurrence of permeation characteristics (especially P-H2 and P-H2/P-N2) near Robeson's upper bound, high thermal stability and good solvent solubility achieved by these structural modifications depicted the potential of this family of polymers as gas separation membrane materials. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Diffusion; Gas permeation; Polybenzimidazole; Sorption; thermal stability

Effect of substituent polarity, bulk, and substitution site toward enhancing gas permeation in dibromohexafluorobisphenol-A based polyarylates - Ishole, Yogesh S.; Karadkar, Prasad R.; Kharul, Ulhas K. (Journal of Polymer Science Part B-Polymer Physics, 2007)
The gas permeation properties of polyarylates were tuned by varying nature and site of substituents present on both of its monomers, viz., bisphenol and dicarboxylic acid. The phenyl rings of hexafluorobisphenol-A were substituted in asymmetric manner by polar bromine to obtain dibromohexafluorobisphenol-A. This bisphenol was polymerized with equimolar mixture of iso- and terephthalic acid (base case), bromo- and nitroterephthalic acid (polar group substituted acids), 4,4'-hexafluoroisopropylidene bis(benzoic acid), and t-butyl isophthalic acid (bulky group containing acids). Physical properties and gas permeation properties of these polyarylates were investigated to assess combined effects of asymmetric nature of bisphenol substitution, polar nature of substituent bromine, hexafluoroisopropylidene group present at the bridge position of bisphenol, and substituent present on the acid moiety. The combination of these substituent types led these polyarylates to lie near Robeson upper bound. The gas sorption analysis and estimation of diffusivity in these polyarylates shed a light on observed variations in gas permeation properties by attempted structural variations. (c) 2007 Wiley Periodicals, Inc.
Keywords: asymmetric substitution; Diffusion; Gas permeation; gas sorption; polyarylates; selectivity; structure-property relations

Effective arsenic removal using polyacrylonitrile-based ultrafiltration (UF) membrane - Lohokare, Harshada R.; Muthu, M. R.; Agarwal, Gopal P.; Kharul, Ulhas K. (Journal of Membrane Science, 2008)
Applicability of polyacrylonitrile (PAN)-based negatively charged ultrafiltration (UF) membrane for effective arsenic removal has been demonstrated, to our knowledge, for the first time. The hydrolysis of PAN-based UF membrane surface by NaOH leading to the formation of carboxylate (-COO-) groups and reduction in initial pore size rendered As-V rejection capability by Donnan exclusion principle. A lowering in pore size was indicated by the reduction in water flux and elevation in rejection of protein and polyethylene glycol (PEG). NaOH treatment leading to formation of carboxylate group on the membrane surface was indicated by FTIR-ATR, while contact angle measurement indicated increased hydrophilicity. This treatment rendered membrane surface smoothening as confirmed by SEM and AFM analyses. The molecular weight cut off after the NaOH treatment was found to be similar to 6 kDa. The rejection of pentavalent arsenic (As-V) by these surface modified membranes was studied with different feed concentration, cross-flow velocity, pressure, temperature and pH. Experiments with 50 ppb As-V in feed showed that arsenic rejection was close to 100% and remained constant up to 6 h. Feed sample concentration of 1000 ppb and 50 ppm of As-V showed >95% rejection at pH 7 and room temperature, but for 1000 ppm feed concentration, the rejection was 40-65%. For concentrations <= 50 ppm of arsenic in the feed, the rejection coefficient was not dependent on cross-flow velocity or transmembrame pressure. The rejection for 1000 ppm. concentration of As-V varied from 40 to 65% with variation in the cross-flow velocity and transmembrane pressure as the concentration polarization was important. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Arsenic rejection; concentration polarization; cross-flow velocity; Polyacrylonitrile; surface modification; Ultrafiltration

Effect of foulants on arsenic rejection via polyacrylonitrile ultrafiltration (UF) membrane - Agarwal, Gopal P.; Karan, Raj; Bharti, Sachin; Kumar, Hemant; Jhunjhunwala, Sumit; Sreekrishnan, T. R.; Kharul, Ulhas K. (Desalination, 2013)
Arsenic rejection via modified polyacrylonitrile ultrafiltration (UF) membrane was found to be very high, however, the presence of commonly found foulants in arsenic solution affected membrane performance. The effect of commonly found foulants, such as ovalbumin, humic acid and egg white on arsenic rejection were studied. Experiments indicated that the As(V) rejection was affected by the total quantity of proteins and not the variety of proteins present in a solution. As(V) rejection was found to decrease with increasing proteins while fouling was found to increase from 25% for 0.1 mg/ml to 33% for 0.5 mg/ml egg white. The As(V) rejection was found to decrease with increasing concentration of humic acid for PAN membranes. Fouling studies showed that humic acid was a lesser foulant in comparison to egg white. However a combination of the two foulants led to a decrease in the overall fouling. pH was also found to be a very important factor for egg white dissolution and As(V) rejection. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Arsenic rejection; Egg white; Humic acid; Ovalbumin; Polyacrylonitrile; Ultrafiltration

Effect of the viscosity of poly(benzimidazole) on the performance of a multifunctional electrocatalyst with an ideal interfacial structure - Balan, Beena K.; Unni, Bipinlal; Chaudhari, Harshal D.; Kharul, Ulhas K.; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2013)
A novel electrocatalyst system with unique multifunctional characteristics, originated by the presence of a proton conducting polybenzimidazole (PBI-BuI) bound layer and electron conducting hollow carbon nanofibers (CNF) with catalytically active Pt nanoparticles, has been devised based on a simple strategy. This was achieved by decorating Pt nanoparticles along the inner cavity, as well as on the outer walls of the hollow CNF support (F-Pt). In a further extension, a low molecular weight PBI, synthesized by optimizing the experimental parameters, was incorporated into the inner cavity and along the outer surfaces of F-Pt. Excellent dispersion of the Pt nanoparticles was achieved by properly utilizing the available carbon surface results in improved electrocatalytic activity, while the CNF backbone ensures high electron conductivity as well. The polymer binder coverage formed along the inner and outer wall surfaces provides an efficient triple phase boundary (TPB) around the Pt nanoparticles to facilitate the electrode reactions. The amount and the viscosity of the PBI-BuI in the electrode material were systematically varied to study the influence on the electrochemical performance. Transmission electron microscopy analysis confirms PBI insertion into the tubular cavity of CNF. Pore size distribution analysis implies that both the viscosity and the amount of PBI-BuI have a pivotal role in defining the microstructure of the electrode. Electrochemical studies using cyclic voltammetry (CV) and rotating disc electrode (RDE) reveal the exceptionally high activity of this hybrid material with an improved electrochemically active area. The significant improvement for the oxygen reduction reaction is further confirmed by the single cell analysis also. The high power density displayed by the PBI-BuI based system, as compared to the Nafion based system, validates the conceptualization of the well controlled triple-phase boundary in the system. These results demonstrate that PBI-BuI has a constructive effect in tuning the electrochemical activity at an optimum amount and at a favourable viscosity of the proton conducting polymer.